Exploration of various visual media (real and virtual) in physics learning - Rifal Ramadhan Rifal; Andi Suhandi; Achmad Samsudin; Lina Aviyanti (Momentum: Physics Education Journal, 2025)
This study aims to explore the role of visual media in physics learning especially in static electricity and capacitors, and to identify the obstacles faced by teachers in using these visual media. This study uses a qualitative descriptive approach with a literature review and analysis of data obtained through a questionnaire distributed to high school physics teachers in Bandung City. The data collected includes the use of various types of visual media, the purpose of their use, students' responses to visual media, and the obstacles faced in their implementation. The findings show that visual media such as PowerPoint, digital simulation (PhET), and animated videos are very effective in physics learning to help students understand abstract concepts, especially in capacitor material. Digital simulation, with an effectiveness rate of 82.4%, proved to be the most effective in explaining the concept of capacitors. The use of this visual media also has a positive impact on student motivation in learning. However, the main obstacles faced are the limitations of time, facilities, and technical skills of teachers in developing visual media. In conclusion, although the use of visual media is very beneficial, further support in the form of training, provision of facilities, and better time management is needed to optimize the application of visual media in physics learning.